The girls with no names [large type] - Burdick, Serena (Thorndike Press Large Print Peer Picks, 2020)
"The Girls with No Names pulls readers into the gilded age of New York City in the 1910s, when suffragettes marched in the street, unions fought for better work conditions--and girls were confined to the House of Mercy for daring to break the rules. Not far from Luella and Effie Tildon's large family mansion in Inwood looms the House of Mercy, a work house for wayward girls. The sisters grow up under its shadow with the understanding that even as wealthy young women, their freedoms come with limits. But when the sisters accidentally discover a shocking secret about their father, Luella, the brazen older sister, becomes emboldened to do as she pleases. But her rebellion comes with consequences, and one morning Luella is mysteriously gone. Effie suspects her father has made good on his threat to send Luella to the House of Mercy and hatches a plan to get herself committed to save her sister. But she made a miscalculation, and with no one to believe her story, Effie's escape from the House of Mercy seems impossible--unless she can trust an enigmatic girl named Mable. As their fates entwine, Mable and Effie must rely on each other and their tenuous friendship to survive. Home for Unwanted Girls meets The Dollhouse in this atmospheric, heartwarming story that explores not only the historical House of Mercy, but the lives--and secrets--of the girls who stayed there."--